Age and moisture affect the relationship between competition and tree growth - Xinyu Han; Lushuang Gao; Mingqian Liu; Yihong Zhu; Keda Cui; Xinyu Zhang; Xiuhai Zhao; Ruibo Zhang; Klaus von Gadow; Yiyu Tian; Kangchen Wang (Global Ecology and Conservation)
The frequent and intensifying droughts caused by climate warming are leading to widespread declines in tree growth and increased mortality, posing a significant threat to the health and vitality of forest ecosystems. While competition among trees is recognized as a critical factor influencing their growth, the precise mechanism underlying its impact remains unclear. Here, we investigate the role of crown size in the process of competition affecting tree growth across varying gradients of age and moisture conditions. Our analysis is based on comprehensive data collected from natural forests of Xing'an larch (Larix gmelinii) located in the northeastern region of China. We observed that competition indirectly impacts tree growth by diminishing crown size, and this influence is modulated by both tree age and environmental moisture conditions. Specifically, mature trees are better able to withstand competition pressure than young trees. The stimulatory effect of crown size on tree growth enhances in young tress, but diminishes in mature trees. Additionally, the negative impact of competition on tree crown size is more pronounced in high moisture regions, and larches experiencing crown reduction under intense competition exhibit a heightened sensitivity to water availability. Our findings provide robust evidence that competition indirectly influences tree growth by modifying their phenotypic traits. Notably, the crown, serving as a crucial organ for nutrient acquisition in trees, was a mediating factor between competition and growth. This result holds significant implications for the sustainable management of forest ecosystems in the face of a warming climate in the future.